Edukasi dan Deteksi Dini Komplikasi Kehamilan dengan Pemeriksaan Laboratorium - Septiyaningsih, Rochany; Kusumawati, Dhiah Dwi; Yunadi, Frisca Dewi; Indratmoko, Septiana (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2020)
The World Health Organization (WHO) states that maternal mortality worldwide due to complications during pregnancy and childbirth in 2017 is estimated at around 810 cases. Between 2000 and 2017 there was a decline in the ratio of MMR around the world by 38%. WHO also states that 94% of global maternal deaths occur in low and middle income countries. In Indonesia, maternal deaths due to complications from pregnancy or childbirth every year are estimated at 20,000 mothers died from five million births. Delivery assistance by trained health workers in health facilities can be an effort to reduce MMR and IMR. In addition, awareness of pregnant women is also important for the importance of having a pregnancy with a health worker. This community service aims to increase the knowledge of pregnant women about anemia and to detect early pregnancy complications by laboratory examinations. The target of this activity is 15 pregnant women. The dedication activity is conducting educational activities, laboratory examinations in Tambakreja Village, Cilacap Regency. Based on the results of this activity it was concluded that there was an increase in knowledge of pregnant women about anemia and found 2 pregnant women experiencing anemia from 15 pregnant women and urine examination found all negative pregnant women